Progressive growth of the solid–electrolyte interphase towards the Si anode interior causes capacity fading - He, Yang; Jiang, Lin; Chen, Tianwu; Xu, Yaobin; Jia, Haiping; Yi, Ran; Xue, Dingchuan; Song, Miao; Genc, Arda; Bouchet-Marquis, Cedric; Pullan, Lee; Tessner, Ted; et al. (Nature nanotechnology, 2021)
The solid–electrolyte interphase (SEI), a layer formed on the electrode surface, is essential for electrochemical reactions in batteries and critically governs the battery stability. Active materials, especially those with extremely high energy density, such as silicon (Si), often inevitably undergo a large volume swing upon ion insertion and extraction, raising a critical question as to how the SEI interactively responds to and evolves with the material and consequently controls the cycling stability of the battery. Here, by integrating sensitive elemental tomography, an advanced algorithm and cryogenic scanning transmission electron microscopy, we unveil, in three dimensions, a correlated structural and chemical evolution of Si and SEI. Corroborated with a chemomechanical model, we demonstrate progressive electrolyte permeation and SEI growth along the percolation channel of the nanovoids due to vacancy injection and condensation during the delithiation process. Consequently, the Si–SEI spatial configuration evolves from the classic ‘core–shell’ structure in the first few cycles to a ‘plum-pudding’ structure following extended cycling, featuring the engulfing of Si domains by the SEI, which leads to the disruption of electron conduction pathways and formation of dead Si, contributing to capacity loss. The spatially coupled interactive evolution model of SEI and active materials, in principle, applies to a broad class of high-capacity electrode materials, leading to a critical insight for remedying the fading of high-capacity electrodes. A correlated structural and chemical evolution of silicon and the solid–electrolyte interphase was unveiled in three dimensions by integrating sensitive elemental tomography, an advanced algorithm and cryogenic scanning transmission electron microscopy.